2011
DOI: 10.1890/es11-00110.1
|View full text |Cite
|
Sign up to set email alerts
|

Landscape context and long-term tree influences shape the dynamics of forest-meadow ecotones in mountain ecosystems

Abstract: Abstract. Forest-meadow ecotones are prominent and dynamic features of mountain ecosystems.Understanding how vegetation changes are shaped by long-term interactions with trees and are mediated by the physical environment is critical to predicting future trends in biological diversity across these landscapes. We examined 26 yr of vegetation change ) across 20 forest-meadow ecotones spanning a range of landforms/hydrologies and elevations (montane and subalpine) in the Three Sisters Biosphere Reserve, Oregon (US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 76 publications
(84 reference statements)
2
17
0
Order By: Relevance
“…This mirrors findings that climate was the most likely driver of woody plant encroachment into other meadow systems (Woodward et al 1995, Dyer and Moffett 1999, Lepofsky et al 2003, Brandt et al 2013, Durak et al 2015, although Takaoka and Swanson (2008) found fire to be of greater importance while Haugo et al (2011) found little evidence of climate influencing recent meadow encroachment. In combination with seed availability, climate was sufficient to explain most variation in encroachment density among meadows, while climate during early life stages was able to explain nearly all historic variation in recruitment timing.…”
Section: Integrationsupporting
confidence: 65%
See 1 more Smart Citation
“…This mirrors findings that climate was the most likely driver of woody plant encroachment into other meadow systems (Woodward et al 1995, Dyer and Moffett 1999, Lepofsky et al 2003, Brandt et al 2013, Durak et al 2015, although Takaoka and Swanson (2008) found fire to be of greater importance while Haugo et al (2011) found little evidence of climate influencing recent meadow encroachment. In combination with seed availability, climate was sufficient to explain most variation in encroachment density among meadows, while climate during early life stages was able to explain nearly all historic variation in recruitment timing.…”
Section: Integrationsupporting
confidence: 65%
“…In many locations, mountain meadows are being transformed by woody plant encroachment (Woodward et al 1995, Dyer and Moffett 1999, Berlow et al 2002, Lepofsky et al 2003, Takaoka and Swanson 2008, Haugo et al 2011, Brandt et al 2013, Durak et al 2015. Conversion of herbaceous meadows into forest could impact hydrologic services by altering soil properties important to water retention and by altering vegetation water use.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is expected to affect alpine and sub-alpine areas [1][2][3][4] and forecasting changes to these areas is critical for natural resource management and conservation. On a warming planet where multiple aspects of climate are changing [5], climate sensitivities that differ among sub-alpine tree species could result in differing growth responses.…”
Section: Introductionmentioning
confidence: 99%
“…On a warming planet where multiple aspects of climate are changing [5], climate sensitivities that differ among sub-alpine tree species could result in differing growth responses. Since sub-alpine trees set the important forest/meadow ecotone at high elevations [4], the drivers of variability in climate-growth responses of sub-alpine tree species may therefore have particular significance for ecosystem function, resource management and conservation (e.g., the amount of carbon stored in trees, the upslope movement of treeline, conversion of alpine habitat to forests). For example, high mountain meadows are species rich (e.g., [6,7]), and-due to their isolation from each other, and the shape of mountains-are likely to decrease in area if sub-alpine tree growth increases greatly with climate warming.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical resistivity tomography is a well-established tool in studies investigating subsurface hydrology (Frohlich, 1994 andRavindran andPrabhu, 2012 (Haugo et al, 2011;Griffiths et al, 2005;Miller and Halpern, 1998). If current climate trends continue, it may become increasingly difficult to restore encroached meadows, as conifer encroachment into meadows may be indicative of a transition to a new stable state (Haugo and Halpern, 2007).…”
Section: Chapter 6 Conclusion and Summarymentioning
confidence: 99%